Given that,
2x + 5y = - 12. ...... (1)
7x - 2y = - 42 ....... (2)
To solve this, we have to cancel one variable. For that, multiply eq(1) with 2 and eq(2) with 5.
2 x (2x + 5y = -12). => 4x + 10y = -24. (iii)
5 x (7x - 2y = -42). => 35x - 10y = -210. (iv)
Now, add left and right sides, we get
(4x + 10y) + (35x - 10y). = -24 -210
4x + 35x + 10y - 10y = -234
39x = -234
x = -234/39
x = -6
Now, put the values in eq(1), we can get the value of y
2(-6) + 5y = -12
-12 + 5y = -12
5y = -12 + 12
5y = 0
y = 0